Social Media and Indian Youth - Bhati, Vikramaditya Singh; Bansal, Jayshri (International Journal of Computer Sciences and Engineering, 2019)
At present Social Media is a part of life for most of the Indian youth. The usage of the Internet is now heavily shifted to Social Media Sites. Undoubtedly Social Media has its own merits, but excessive use of Social Media is affecting the lifestyle of youth moreover, statistics show that addiction to social media resulted in increased health problems and change in behavior. Most of the previous work done in this field relates to foreign countries. This paper focus on the Impact of Social Media Sites on youth, good, bad & major concerns in Indian perspective.